What drives retailer loyalty? A meta-analysis of the role of cognitive, affective, and social factors across five decades - Liu-Thompkins, Yuping; Khoshghadam, Leila; Attar Shoushtari, Arjang; Zal, Saeed (Journal of Retailing, 2022)
Today's retailers face significant competition due to the proliferation of both retail formats and channels. It is crucial for retailers to understand how to develop a loyal customer base for competitive advantage. To this end, we conducted a meta-analysis of 1,908 effect sizes from 319 studies on retailer loyalty over the last 50 years, to examine the impact of cognitive, affective, and social retail experience on customer loyalty toward a retailer. Our analysis shows that affective experience became more important over time and had the highest impact on retailer loyalty, 24% more than that of social drivers and 50% more than cognitive drivers. Affective experience is particularly impactful online and for retailers of hedonic or low-involvement products. Social drivers increased significantly in impact over time too. Its effect was particularly strong on attitudinal loyalty, for studies with a higher proportion of females, and surprisingly, in utilitarian rather than hedonic retail contexts. Taken together, our findings suggest that traditional cognitive differentiators such as price and product assortment are no longer sufficient for maintaining customer loyalty to a retailer. Positive affective and/or social experience represent a more defensible path toward customer loyalty.
Keywords: affect; cognition; dept.mrk; meta-analysis; peer-reviewed; retailer loyalty; retailing; social interaction